Relations between perceived teacher's autonomy support, cognitive appraisals and boredom in physics learning among lower secondary school students - Margaret Ekatushabe; Diana Kwarikunda; Charles M. Muwonge; Joseph Ssenyonga; Ulrich Schiefele (SpringerOpen, 2021)
Abstract Background Boredom during learning activities has the potential of impeding attention, motivation, learning and eventually achievement. Yet, research focusing on its possible antecedents seems to have received less attention especially within the physics domain. Based on assumptions of the Control Value Theory of Achievement Emotions (CVTAE), this study aimed at examining gender differences and structural relationships between students' reported perceived teacher autonomy support (PTAS), cognitive appraisals (self-efficacy and task value) and learning-related boredom in physics. A sample of 375 (56% females) randomly selected 9th grade students (mean age = 15.03 years; SD = 1.02) from five secondary schools in Masaka district of Uganda took part in the study. Results Data collected from students' self-reports using standardised instruments revealed that higher levels of PTAS, self-efficacy, and task value were significantly associated with lower levels of boredom during physics learning. Females reported significantly greater task value for learning physics than the males. Self-efficacy (β = − .10, p < .05) and task value (β = − .09, p < .01) partially mediated the relationship between PTAS and boredom. PTAS showed significant direct negative contributions to boredom (β = − .34, p < .001). Conclusion These findings provide support for theory and practice about the importance of promoting autonomy among students by adjusting instructional behaviours among teachers of physics. Teacher autonomy supportive behaviours influence formation of students' beliefs about ability, subjective value and learning-related boredom in physics. Implications and suggestions for further research are also discussed in this paper.